Development of an Online Automatic Computed Radiography Dose Data Mining Program: A Preliminary Study - Ng, Curtise; Sun, Zhonghua (Elsevier Ireland Ltd, 2010)
Recent studies have reported the computed radiography (CR) dose creep problem and therefore the need to have monitoring processes in place in clinical departments. The objective of this study is to provide a better technological solution to implement a regular CR dose monitoring process. An online automatic CR dose data mining program which can be applied to different systems was developed based on freeware and existing softwares in the Picture Archiving and Communication System (PACS) server. The program was tested with 69 CR images. This preliminary study shows that the program addresses the major weaknesses of some existing studies including involvement of manual procedures in the monitoring process and being only applicable to a single manufacturer's CR images. The proposed method provides an efficient and effective solution to implement a CR dose monitoring program regularly in busy clinical departments to regulate the dose creep problem so as to reinforce the As Low As Reasonably Achievable (ALARA) principle.